2018
DOI: 10.1097/md.0000000000013901
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting labor duration in Chinese pregnant women

Abstract: The aim of the study was to explore the role of parity, maternal age, medical interventions, and birth weight with respect to labor duration and cervical dilation. A total of 1601 pregnant women who had a singleton term gestation, spontaneous onset of labor, vertex presentation, vaginal delivery, and a normal perinatal outcome were reviewed. The retrospective study was conducted in patients from West China Second University Hospital of Sichuan University during June 2008 to June 2013. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
1
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 27 publications
1
25
1
3
Order By: Relevance
“…Secondly, the results of our study demonstrated that labour duration was significantly longer in nulliparous women than that in multiparous women, which was consistent with Chen et al's finding [39]. Concurrently, durations of the first, second, and total stage of labour in our study was similar to those reported by Chen et al [39].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Secondly, the results of our study demonstrated that labour duration was significantly longer in nulliparous women than that in multiparous women, which was consistent with Chen et al's finding [39]. Concurrently, durations of the first, second, and total stage of labour in our study was similar to those reported by Chen et al [39].…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, however, Vadivelu et al have shown that amniotomy was associated with a shorter labour duration compared with conservative management in women with singleton pregnancies [42]. Conversely, Chen et al found that in nulliparas, the average time of first stage of labour and total labour duration increased due to amniotomy [39]. The association between amniotomy and labour duration varied due to different research designs and inter-study heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 8 ] For most parturients, experiencing pain during delivery is an important reason why they choose cesarean section; conversely, for obstetricians and midwives, standards and treatment during the labor process are other important reasons for choosing cesarean section. [ 9 11 ] The obstetric group of the Chinese Society of Anesthesiology has performed a series of surveys on labor analgesia across the country, polling 42 maternity hospitals (divided into seven groups according to their geographical locations), which included 1,489,228 delivery cases in 3 years. [ 12 ] The labor analgesia rates were listed as follows: 11.65% in northeast China, 29.97% in northern China, 30.77% in east China, 17.97% in north China, 11.65% in southern China, 19.66% in central China, 1.02% in northwest China, and 7.56% in southwest China (unpublished).…”
mentioning
confidence: 99%
“…Secondly, cervix has the ability to adjust the position of fetal head, and an incomplete cervix can in uence position of fetal head which is more likely to lead a cephalic presentation dystocia. In addition, women with a prior cervical excision procedure were elder in our study, who might undergo a physiologic aging process of myometrial tissues and skeletal muscle [17]. Those three reasons may prolong the duration of the second stage of labor.…”
Section: Discussionmentioning
confidence: 96%